COVID 19 SPREAD PREVENTION AND CONTROL MEASURES: EMERGENCY CENTER OF THE UNIVERSITY CLINICAL CENTER OF SERBIA - Mioljevic, Vesna; Ercegovac, Marko; Gregorić, Pavle; Jovanović, Dušan; Tulić, Goran; Jovanović, Snežana; Vukašinović, Stevana; Vukašinović, Stevana (Srpski medicinski časopis Lekarske komore, 2021)
COVID 19 SPREAD PREVENTION AND CONTROL MEASURES:EMERGENCY CENTER OF THE UNIVERSITY CLINICALCENTER OF SERBIA INTRODUCTION:The pandemic caused by the SARS CoV2 virus changed people's lives and their habits, introduced limitations in everyday life and brought uncertainty and a new dimension of understanding reality and caring for one's own health to all of humanity in the 21st century. It is in the world until June 14, 2021. 175, 541,600 people were infected and about 3,798.36 million people died, while in Serbia until June 14, 2021. 715,604 were infected and 6,990 thousand people died.OBJECTIVES:Present the manner of organizing the epidemiological surveillance of the Epidemiology Service of the University Clinical Center of Serbia (UKCS) at the Emergency Center of the UKCS as well as the application of measures to prevent and control the spread of COVID 19Show the method of triage of patients with suspected COVID 19 in the Emergency Center UKCSMETHODOLOGY:Instructions for the rational use of personal protective equipment in health care institutions, depending on the activities performed.https://www.cdc.gov/coronavirus/2019-ncov/.Center for Disease Control, Atlanta.RESULTS:An Algorithm for procedures for patients with suspected and proven infection on COVID 19 for patients of the Emergency Center of Serbia has been formed. This algorithm has been applied since March 1, 2021. in the Triage Service of the Admission Clinic UC UKCS. In addition to this Algorithm, screening of medical staff for SARS CoV2 was performed by sampling nasopharyngeal and goiter swabs (for PCR analysis and antigen tests) and blood for serological analyzes.CONCLUSION:In less than a year, humanity has managed to start a long and difficult fight with the virus, but with a powerful weapon - the vaccine. In addition to vaccination, which is undoubtedly the most important measure to prevent COVID 19, our responsible behavior (wearing masks, hand hygiene, respecting physical distance), especially in this period of increasing the number of patients and the emergence of new strains, is also an important measure to prevent and control the spread of COVID 19 .KEY WORDS: Covid 19,  epidemiology, prevention
Keywords: COVID-19; epidemiological surveillance; prevention; Serbia